The Development of Media Literacy among Grade Five Teachers and Students - A Case Study - Rachel McCabe; Winston Emery (The Canadian Network for Innovation in Education (CNIE), 2008)
This is the first of two articles about a study of the implementation of a media literacy curriculum project in three inner city school Grade 5's in Montreal. The authors describe what the teachers and students learned about two key Media Literacy concepts: the media construct reality and audiences negotiate the meanings of media texts. The teaching featured the use of Internet and computer technology. Their findings suggest that it is possible to teach elementary students to read media critically and raises some issues that merit further investigation: the ideology of positivism that permeates the use of technology in education; the training of media education teachers; and the factors that characterize effective media education pedagogy.